Teaching Methods Preference By Medical Students In A Malaysian Public University - Norhasiza, Mat Jusoh; Harafinova, Harman Shah; Myat Moe Thwe, Aung; Aniza, Abd Aziz; Norwati, Daud (2017)
Bachelor of Medicine & Bachelor of Surgery (MBBS) programme in Universiti Sultan Zainal Abidin (UniSZA) started in 2009. Its curriculum uses many different types of teaching method during clinical years. There is a strong association between teaching methods and apprehension of knowledge by students. The curriculum is currently at a review process. An online survey was conducted to evaluate graduating medical students’ satisfaction on various teaching methods during clinical years of the existing curriculum. An anonymous online feedback on the MBBS curriculum UniSZA was done on 56 final year students who have just graduated. A scale of one to five was used to determine their satisfaction on teaching methods in clinical year. Scale one represents ‘very dissatisfied’ while scale five is meant for ‘very satisfied’. Microsoft Excel Programme was used for descriptive analysis. All 56 students gave their feedbacks. 71.4% of them were female students. Students’ satisfaction on the teaching methods is presented as mean (SD) score. All 56 students gave their feedbacks. 71.4% of them were female students. Students’ satisfaction on the teaching methods is presented as mean (SD) score. All teaching methods were scored above 4.0. The results showed that the scores in descending order were; bed side teaching 4.59 (0.50), lecture 4.50 (0.51), case discussion 4.46 (0.57), ward round 4.46 (0.66), practical session 4.45 (0.63), clinical skill lab 4.45 (0.63), film viewing 4.43 (0.57), projected material quiz 4.41 (0.60), clinical problem solving 4.34 (0.67), seminar 4.30 (0.71), ward work 4.29 (0.68), tutorial 4.27 (0.62), clinical case correlation 4.23 (0.79), on-call 4.05 (0.84).Students’ satisfaction on the number of students for each teaching session was 4.4 (0.54). The level of satisfaction of graduating medical students on the existing teaching methods is reasonably high. Most students are preferred teacher-centred learning teaching methods as evidence by high satisfaction scores on bed side teaching followed by lecture. The low satisfaction scores are majority student-centred learning teaching methods. This feedback will help the faculty in revising and improving their teaching methods of the future curriculum.